2022
DOI: 10.1177/00031348221114039
|View full text |Cite
|
Sign up to set email alerts
|

The State of the LGBTQ+ Community in Surgery

Abstract: The LGBTQ+ community is a diverse community that faces unique needs and multidimensional form of discrimination. Cultural awareness and awareness of intersectionality of experiences are essential in creating an equitable environment for health care professionals and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…We agree that the continuing marginalization, discrimination, and stigma against the SGM community adversely impact both SGM providers and patients. 1 It is with the great support of Pascarella’s thoughtful discourse and recommendations that we would like to make some contributions, further expanding on the disparities in medicine for physicians and patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We agree that the continuing marginalization, discrimination, and stigma against the SGM community adversely impact both SGM providers and patients. 1 It is with the great support of Pascarella’s thoughtful discourse and recommendations that we would like to make some contributions, further expanding on the disparities in medicine for physicians and patients.…”
mentioning
confidence: 99%
“…Finally, uplifting the experiences of SGM patients in this discussion is also important, particularly when considering the numerous health disparities that SGM populations face in both healthcare access and delivery. 1 When compared to heterosexual/cisgender counterparts, SGM individuals have higher rates of cardiovascular disease, diabetes, obesity, asthma, certain cancers, substance use disorders, cigarette smoking, and suicide. 4 In part, these disparities are due to factors within the healthcare system, such as previous negative experiences, perceived discrimination, provider biases, and lower or limited access to care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Unfortunately, a lack of trust in the healthcare system, denial of care, discrimination, and violence discourage individuals who identify as LGBTQIA+ from seeking treatment. 19 A 2020 study from the Center for American Progress 20 reported that 15% of patients who identify as LGBTQIA+ postponed medical care due to discrimination. For example, an Act in Arkansas passed in 2021 allows clinicians to refuse to provide medical treatment because of religious or moral objections.…”
mentioning
confidence: 99%